Influencia del consumo de alcohol en conflictos de pareja. Hospital Básico 11 B.C.B. “Galápagos”. Riobamba, 2018-2019 - Méndez Rivera, Evelyn Catherine (2019)
The present study is about influence of alcohol consumption in partner conflicts, made at the primary Hospital 11 B.C.B. "Galapagos" in Riobamba aimed at analyzing the impact of alcohol consumption in partner conflicts, based on medical records and statistical indicators that currently alert public health due to the high percentages. The research was based on the quantitative approach, was documentary, bibliographic, retrospective and descriptive by exclusive design, not experimental. The sample was intentional non-probabilistic, made up of 156 patients (of a population of 1119, medical records), attended in the periods: July-November 2017 and January-December 2018. An observation sheet was used for data logging and tabulation for the collection of demographic and clinical data and the statistical package SPSS version 24.00. IBM for statistical analysis with the following results: 31% of the population served corresponded to soldiers over 40 years of age in the active and passive service; concerning the second variable 98.7% experienced couple conflicts. Of relation of the variables 21.2% showed alcohol consumption and conflict of couple. Regarding Comorbidity 7.2% presented a diagnosis of "mild depressive episode", followed by 2.6% with diagnosis "mixed anxiety-depressive Disorder". Results that confirm the behavioral problems in our social context deepen at the same time. It is essential to give due importance to prevention.